An Evaluation of Hepatitis C Virus Telehealth Services Serving Tribal Communities: Patterns of Usage, Evolving Needs, and Barriers. (September 2019) - Stephens, David; Leston, Jessica; Terrault, Norah A.; Gailloux, Keri; Mera, Jorge; Essex, Whitney; Reilley, Brigg
Abstract : Introduction: American Indian/Alaska Native (AI/AN) populations are disproportionately affected by chronic hepatitis C virus (HCV) infection. Federal facilities of the Indian Health Service, in conjunction with Tribally operated and Urban Indian (I/T/U) health care facilities, serve an estimated 2.2 million AI/AN patients. The facilities are mainly rural and have few specialists. To fill the gap in specialists in I/T/U clinics, the Extension for Community Healthcare Outcomes (ECHO) telehealth model was used to support clinicians to treat HCV in primary care. Methods: Participants in 3 regional HCV ECHO networks serving AI/AN patients were surveyed by e-mail and text message to determine patterns of ECHO usage, usefulness, and barriers to treating patients with HCV at their primary care clinics. Results: From a total of 44 respondents from 72 eligible health care facilities, a majority (61%) stated that they started treating patients with HCV subsequent to participating in the telehealth program. Participants with more telehealth experience sought increasing complexity in patient case presentations. In California, 7 of 8 clinicians who had attended more than 10 ECHO sessions expressed diminishing need for ECHO sessions to manage cases (<25% of patients). All elements of the ECHO sessions (presenting patient cases, listening to patient case presentations, teaching sessions, and sharing of programmatic insights) were considered "extremely useful" by the majority of respondents. The factors most cited as moderate or extensive barriers to providing HCV care were access to HCV direct acting antivirals (60%) and linking patients to care (50%). Discussion: Extension for Community Healthcare Outcomes may play a key role not only in increasing clinical capacity for HCV treatment but also in the inception of HCV services in this sample of I/T/U facilities. Participants with more telehealth experience demonstrated signs of increasing clinical capacity, where they were more likely to seek complex patient case presentations in ECHO sessions. A number of barriers continue to keep AI/ANs from being cured and stop clinicians from ending the epidemic, including access to HCV medications, time to provide HCV clinical services, and linking patients to HCV services. Abstract : Supplemental Digital Content is Available in the Text.